VI Certamen Crono-Teatro (2019). Modalidad del tren. 2. Próxima Estación, Maletón - Martínez, Elena (Pygmalion. Revista de teatro general y comparado, 2025)
VI Certamen Crono-Teatro (2019). Modalidad del tren. 2. Próxima Estación, Maletón